2007
DOI: 10.1111/j.1746-1561.2007.00238.x
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated School Health Programs and Academic Achievement: A Systematic Review of the Literature

Abstract: BACKGROUND: Few evaluations of school health programs measure academic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
175
1
8

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(192 citation statements)
references
References 38 publications
5
175
1
8
Order By: Relevance
“…www.erudit.org | 37 introduction La collaboration Communauté-École à partir de l'élève L'implantation du Programme de formation de l' école québécoise constitue une tentative d' effectuer un virage socio-constructiviste dans la façon de concevoir l' éducation au Québec (Lenoir, Larose, Lessard, 2005). Cette évolution fondamentale sur le plan épistémologique (au moins en principe) est également soutenue par des configurations sociales appelant la modification même de la mission de l' école, dont on lui demande de plus en plus de jouer un rôle accru en matière de socialisation (Lenoir, 2010) ou d' éducation à la santé (Murray et al, 2007), par exemple. En fait, l' école est de plus en plus considérée comme un lieu privilégié et efficace pour atteindre les jeunes à propos d' objets historiquement peu ou pas scolaires (World Health Organization, 2003).…”
Section: Résumé De L'articleunclassified
“…www.erudit.org | 37 introduction La collaboration Communauté-École à partir de l'élève L'implantation du Programme de formation de l' école québécoise constitue une tentative d' effectuer un virage socio-constructiviste dans la façon de concevoir l' éducation au Québec (Lenoir, Larose, Lessard, 2005). Cette évolution fondamentale sur le plan épistémologique (au moins en principe) est également soutenue par des configurations sociales appelant la modification même de la mission de l' école, dont on lui demande de plus en plus de jouer un rôle accru en matière de socialisation (Lenoir, 2010) ou d' éducation à la santé (Murray et al, 2007), par exemple. En fait, l' école est de plus en plus considérée comme un lieu privilégié et efficace pour atteindre les jeunes à propos d' objets historiquement peu ou pas scolaires (World Health Organization, 2003).…”
Section: Résumé De L'articleunclassified
“…A literature review conducted by the Division of Adolescent and School Health of the Centers for Disease Control and Prevention identified school-based health promotional interventions that not only improved health attitudes and behaviors but also improved academic performance. 43 A New York comparison study revealed that students in schools with SBHCs had greater satisfaction with their learning environment, compared with students in schools without SBHCs. 44 Thus, in addition to addressing health promotion by using Bright Futures guidelines for health examinations, SBHCs are increasingly using small group, classroom, and schoolwide evidence-based curricula and interventions to better reach Bright Futures goals for health.…”
Section: The Role Of the Sbhc In Increasing Access To Health Carementioning
confidence: 99%
“…In a recent literature review Murray et al [18] reported findings of 17 coordinated school health programs on academic achievement and concluded that there is little but promising evidence (e.g. a positive effect in low income asthmatic children and a lack of negative effects).…”
Section: Introductionmentioning
confidence: 99%